(3eSfO GdEeGe CMeO Hf MfHds - (3GdTjHGfj, GdeQhRj, GdHZOGOj, CHh YHO Gddg, CMeO Hf eMeO Hf MfHd, J (B241(3g`s
(3ChdgG (B:s
(3gPG eSfO YGFTI QVj Gddg YfgG CNHQfG GHf gdGd CHh jcQ CMeO Hf eGdc aj eSLOg cJGHI bQGAI Ydjg bGd (B: (3KfG CHh YHO GdQMef Hf CMeO Hf eMeO Hf MfHd QMeg Gddg bGd MOKfj Yf YGFTI QVj Gddg YfgG Cf QShd Gddg Udi Gddg Ydjg hSde fgi Yf bJd MjGJ GdHjhJs
(3BNQgG (B:s
(3bGd GdfGS jG QShd Gddg Efc SLOJ Hjf XgQj UdGJc SLOI CWdJgG MJi XffG Gfg bGd CMOK aj CeQ Ch Cfg jhMi Edjc bGd (B: (3cd Pdc de jcf hdcf CHfj GQJMdfj acQgJ Cf CYLdg MJi jaVj MGLJg gPG BNQ eSfO GdfSGA QVj Gddg JYGdi Yfgf CLeYjf (B( (3cPG (B) (3ef cJGH CHj HcQ Hf eGdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 203s
(3eYLe GdeDdajf (B1 / 261s
(3cTa GdXfhf (B2 / 1680s
(3JGQjN GdESdGe (B/ (3hajGJ (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs